2000
DOI: 10.1055/s-2000-8348
|View full text |Cite
|
Sign up to set email alerts
|

Role of Electrophysiological Studies and Arrhythmia Intervention in Repairing Ebstein's Anomaly

Abstract: We conclude that detailed preoperative electrophysiological evaluation in patients with Ebstein's anomaly is mandatory. Aggressive surgical intervention of the associated arrhythmias in addition to anatomic correction can reduce the sudden death in Ebstein's anomaly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 9 publications
(13 reference statements)
1
12
0
1
Order By: Relevance
“…484 In a series of patients undergoing repair of Ebstein anomaly, patients who underwent preoperative EP study with intraoperative ablation of arrhythmia substrate had lower risk of SCD than patients without arrhythmia intervention. 479 In patients with Ebstein anomaly undergoing planned surgical intervention, an integrated approach of arrhythmia intervention has been demonstrated to be safe and effective.…”
Section: -485mentioning
confidence: 99%
See 1 more Smart Citation
“…484 In a series of patients undergoing repair of Ebstein anomaly, patients who underwent preoperative EP study with intraoperative ablation of arrhythmia substrate had lower risk of SCD than patients without arrhythmia intervention. 479 In patients with Ebstein anomaly undergoing planned surgical intervention, an integrated approach of arrhythmia intervention has been demonstrated to be safe and effective.…”
Section: -485mentioning
confidence: 99%
“…are more common in patients with longer-duration persistent AF or more dilated left atria or when linear ablation lesions are used. [333][334][335][336][337][338] Non-reentrant focal arrhythmias often originate at lesion edges or reconnected segments of prior isolated pulmonary veins. 333 Reisolation of the pulmonary vein and ablation of any nonpulmonary vein foci are often effective in treating these arrhythmias.…”
Section: Non-isthmus-dependent Atrial Fluttersmentioning
confidence: 99%
“…Repairing Ebstein's anomaly without correction of associated arrhytmia may result in sudden death. Catheter or surgical ablation is indicated for various symptomatic tachyarrhythmias in Ebstein's anomaly [4].…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Okishige et al reported a case of Ebstein anomaly in which catheter ablation for common atrial flutter was performed; 4 in that case, the atrial flutter cycle length was 312 ms and the flutter waves were wider and deeper on the 12-lead ECG. The unusually slow conduction in the right atrium of the present patient may have been caused by changes in the myocardium, such as fibrosis and dilatation, and the atypical flutter wave possibly resulted from the enlargement and distortion of the atria.…”
Section: Discussionmentioning
confidence: 99%